A STUDY ON KAIROS EXEKIAS’S AMPHORA DEPICTING ACHILLES SLAYING PENTHESILEIA (VI CENT. BC) - Figueira, Ana (2023)
Even though many specialized studies have contributed to the conceptual framework of kairos, there has been very little research dealing with this notion in ancient arts. Observing this gap, principally in what concerns Greek pottery, the author explores Exekias’s pictorial rendition of Achilles slaying Penthesileia in a black fgure amphora dating from VI BC, in order to draw attention to the hermeneutical possibilities arising from a comparatist approach interested in the interaction between words and images. Specifcally, the author proposes that vase fgurations contribute to rethink kairos, principally in what concerns the chain of meaning generated by the association of pictorial materials and ancient philosophy, including key-terms from early Hippocratic medicine, such as that of krisis.